2014
DOI: 10.4049/jimmunol.1302159
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine Cooperativity Is Caused by Competitive Glycosaminoglycan Binding

Abstract: Chemokines comprise a family of secreted proteins that activate G protein-coupled chemokine receptors and thereby control the migration of leukocytes during inflammation or immune surveillance. The positional information required for such migratory behavior is governed by the binding of chemokines to membrane-tethered glycosaminoglycans (GAGs), which establishes a chemokine concentration gradient. An often-observed but incompletely understood behavior of chemokines is the ability of unrelated chemokines to enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 46 publications
3
32
0
Order By: Relevance
“…Both CCL21 and CCL19 bound to a hexasaccharide as observed by SPR analysis (220). GAG binding also plays an essential role in chemokine cooperativity (221). In the absence of cooperative chemokines, CCL19 and CCL21 bound to CCR7 or GAGs on the endothelial cell surface.…”
Section: Consequences Of Ccl19 and Ccl21 Binding To Glycosaminoglycansmentioning
confidence: 87%
“…Both CCL21 and CCL19 bound to a hexasaccharide as observed by SPR analysis (220). GAG binding also plays an essential role in chemokine cooperativity (221). In the absence of cooperative chemokines, CCL19 and CCL21 bound to CCR7 or GAGs on the endothelial cell surface.…”
Section: Consequences Of Ccl19 and Ccl21 Binding To Glycosaminoglycansmentioning
confidence: 87%
“…Recently, Verkar et al demonstrated that chemokine cooperativity is not strictly dependent on the receptor of the cooperative chemokine, but can originate from chemokine heterodimerization or from their binding to membrane-tethered glycosaminoglycans (GAGs), which establishes a chemokine concentration gradient(42). In this respect, the CCR2 ligands CCL2, binds to several GAGs with relatively high affinity(3741).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that the phenomenon of chemokine cooperativity, in which one chemokine can enhance the activity of a second, is due to competition for matrix GAGs, rather than downstream signaling pathway convergence or heterodimerization (Verkaar et al, 2014).…”
Section: Heparin and Cytokines Growth Factors Selectins And Promentioning
confidence: 99%